Identification of a Novel Cellular TPR-Containing Protein, SGT, That Interacts with the Nonstructural Protein NS1 of Parvovirus H-1 - Cziepluch, Celina (American Society for Microbiology, 1998)
The nonstructural protein NS1 of autonomous parvoviruses is essential for viral DNA amplification and gene expression and is also the major cytopathic effector of these viruses. NS1 acts as nickase, helicase, and ATPase and upregulates P38-driven transcription of the capsid genes. We report here the identification of a novel cellular protein that interacts with NS1 from parvovirus H-1 and which we termed SGT, for small glutamine-rich tetratricopeptide repeat (TPR)-containing protein. The cDNA encoding full-length SGT was isolated through a two-hybrid screen with, as bait, the truncated NS1dlC69 polypeptide, which lacks the C-terminal transactivation domain of NS1. Full-length NS1 and SGT interacted in the two-hybrid system and in an in vitro interaction assay. Northern blot analysis revealed one major transcript of about 2 kb that was present in all rat tissues investigated. Rat sgt cDNA coded for 314 amino acids, and the protein migrated in sodium dodecyl sulfate-polyacrylamide gel electrophoresis with an apparent molecular mass of 34 kDa. SGT could be detected in both the nucleus and the cytoplasm of rat cells, as determined by indirect immunofluorescence analysis and Western blotting of fractionated cellular extracts with an affinity-purified antiserum raised against recombinant SGT (AC1.1). In H-1 virus-infected rat and human cells, compared to mock-infected controls, differences in the migration of SGT polypeptides were revealed after Western blot analysis of total cellular extracts. Moreover, the transient expression of NS proteins was sufficient to induce SGT modification. These results show that cellular SGT, which we have identified as an NS1-interacting protein, is modified by parvovirus infection as well as NS expression.